Malarz życia ponowoczesnego. O fotografiach Michaela Wolfa - Kasperek, Ewa (Wydawnictwo Wydziału Nauk Społecznych Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
The painter of postmodern life. On Michael Wolf’s photographs The essay presents the work of contemporary German photographer Michael Wolf, acclaimed for his Series of Unfortunate Events originating from Google Street View photos. The recurring motifs of Wolf’s projects discussed in the text include the problem of public voyeurism, a tension between reality and fiction as well as the role of the artist perceived as a copyist/original author.
Keywords: fotografia; sztuka zawłaszczania; voyeuryzm; flâneryzm; Google Street View